1978
DOI: 10.1002/ijc.2910220506
|View full text |Cite
|
Sign up to set email alerts
|

Frequent elevation of tissue polypeptide antigen in the sera of workers exposed to bladder carcinogens

Abstract: A group of 108 male workers previously exposed to bladder carcinogens and a group of 26 patients with carcinoma of the bladder differed significantly from a control group comprising 63 healthy male donors with respect to their levels of tissue polypeptide antigen (TPA). The risk group exhibited 4-6 times more frequent elevations of TPA than did the group of healthy donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
2

Year Published

1980
1980
1995
1995

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…We recently reported that this indeed is the case, as among apparently healthy chemical work ers the cellular immune reactivity against an allogeneic bladder carcinoma is elevated and comparable to a group of bladder cancer patients [Taylor et al, 1979], In addition, the serum level of tissue polypeptide an tigen (TPA) was also more frequently elevated in the sera of bladder cancer patients and chemical workers than normal donors [Kumar et al, 1978], This study compares the humoral immune response of individuals with known exposure to bladder carcinogens, with a group of bladder cancer patients and with normal donors. Previous work suggested that the sera of can cer patients with a variety of neoplasms contained tumour-specific antibodies.…”
Section: Introductionmentioning
confidence: 95%
“…We recently reported that this indeed is the case, as among apparently healthy chemical work ers the cellular immune reactivity against an allogeneic bladder carcinoma is elevated and comparable to a group of bladder cancer patients [Taylor et al, 1979], In addition, the serum level of tissue polypeptide an tigen (TPA) was also more frequently elevated in the sera of bladder cancer patients and chemical workers than normal donors [Kumar et al, 1978], This study compares the humoral immune response of individuals with known exposure to bladder carcinogens, with a group of bladder cancer patients and with normal donors. Previous work suggested that the sera of can cer patients with a variety of neoplasms contained tumour-specific antibodies.…”
Section: Introductionmentioning
confidence: 95%
“…It has been found that sera from apparently healthy male workers exposed to bladder carcinogens contained significantly raised levels of TPA compared with age-matched healthy volunteers (Kumar et al 1978). A pilot study of TPA concentration in 24-hour urine samples in patients with urothelial neoplasia gave very promising results (Kumar et al 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Es liegt zu diesem Zeitpunkt bereits eine beachtliche Anzahl von wissenschaftlichen Mitteilungen zum TPA vor, wobei insbesondere die Verwendung des Proli ferationsmarkers als Tumormarker Inhalt der meisten Veröf fentlichungen war [1,5, 7,10,12,18-21,23-32, 35-38, 42-44], Die bisher umfangreichsten publizierten Untersuchungsserien wurden von Björklund et al [1] mit 1483 Untersuchungen und von Mross et al [25] mit 1175 Untersuchungen vorgelegt. TPA-Ergebnisse bei nichtmalignen Erkrankungen liegen ebenfalls für Autoimmunerkrankungen [34], nicht maligne Erkrankungen der Mamma [44] und Arbeitern, die Karzino genen ausgesetzt waren [14], vor, wie auch biochemische und proteinchemische Analysen des TPA erfolgt sind [16,17,26,33,40]. Auch erste immunhistologische Arbeiten sind publi ziert worden [2,3,6], so daß seit der Vorstellung des TPARadioimmunoassays 1979 durch Wiklund et al [41], der die Hämagglutinationstechnik ablöste, innerhalb von vier Jahren ein relativ großes Datenmaterial vorliegt.…”
Section: Introductionunclassified